Strategies for Cultivating Anti-Corruption Self-Awareness in Higher Education Learning - Soraya, Nyayu; Maryamah; Syarnubi; Septia Fahiroh (Tadrib: Jurnal Pendidikan Agama Islam, 2025)
This study aims to explore the strategic implementation of anti-corruption self-awareness cultivation in the learning process within the Islamic Education Program at UIN Raden Fatah Palembang. Corruption in Indonesia, including among students, is often characterized by behaviors such as cheating, proxy attendance, and data manipulation, making anti-corruption education crucial. This research uses a descriptive qualitative method, with interviews, observations, and documentation as data collection techniques. The results indicate that values such as honesty, integrity, transparency, and accountability are not only integrated into the curriculum but also implemented through experiential learning strategies, reflective approaches, and assessment methods that promote academic integrity. Lecturers have adjusted their teaching and assessment methods by emphasizing independence and honesty. Additionally, case-based discussions and in-depth reflections in the classroom help students develop awareness of anti-corruption values. The effectiveness of these strategies is evident, as students demonstrate positive behavior, such as avoiding cheating, proxy attendance, and data manipulation, reflecting the successful implementation of these values.